Nature of self esteem and resilience amongst orphans in Kadoma - Patchway Zimbabwe - Madziwabende, Vimbai Moreblessing (Midlands State University, 2020)
This research was on the nature of self-esteem and resilience amongst orphans in Kadoma-Patchway Mashonaland West.The purpose of the study was to reveal the nature of self-esteem and resilience amongst orphans and to find out if the two had relationship. Problems in self evaluations and adjustments to life situation after losing parents amongst orphans motivated the researcher to study on orphans. Age, gender, age at time of loss and strong and weak peer family network appeared to be influential. The study made use of correlational research which was quantitative approach. The target population of this study was 360 orphans. A sample of 120 participants was calculated using the formula a third of the target population. From the selected sample questionnaires were issued. Research instruments used were adopted from Rosenberg, and Smith and colleagues. Data was presented in the form of graphs, pie charts, cross tabulations and Pearson correlation coefficient and analysed using SPSS. Findings from the study indicated that, males have high and moderate resilience than females. It was also demonstrated that orphans who lost their parents between the age of 0-6 years and those with strong peer family network had high self-esteem and resilience as compared to those who lost their parents between the age of 7-17 years and with weak peer family network. The research concluded that the majority of orphans had low self-esteem and low resilience. The findings also indicated there was positive correlation between self-esteem and resilience.